2023
DOI: 10.3389/fsufs.2023.1058977
|View full text |Cite
|
Sign up to set email alerts
|

Foodborne disease hazards and burden in Ethiopia: A systematic literature review, 1990–2019

Abstract: BackgroundFoodborne disease (FBD) affects millions of people each year, posing a health burden similar to malaria, tuberculosis or HIV. A recent World Bank study estimated the productivity losses alone attributed to unsafe food within Africa at $20 billion in 2016, and the cost of treating these illnesses at an additional $3.5 billion. Ethiopia faces multiple food safety challenges due to lack of infrastructure and basic pre-requisites for food safety such as clean water and environment, washing facilities, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 125 publications
0
2
0
Order By: Relevance
“…Our findings indicated that a variety of food samples were reported contaminated with food hazards reflecting the need to target different food value chainsincluding beef, poultry, pork, vegetables, cereals, fruits and water-for food safety interventions. Consistent with our findings, a review on food hazards in Ethiopia showed that food contamination with hazards is common in beef, poultry and vegetable food value chains (Gazu et al, 2023). The widespread contamination of foods with hazards in the country raises public health concerns, especially for vulnerable groups such as children, the elderly, pregnant women and the immunocompromised.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings indicated that a variety of food samples were reported contaminated with food hazards reflecting the need to target different food value chainsincluding beef, poultry, pork, vegetables, cereals, fruits and water-for food safety interventions. Consistent with our findings, a review on food hazards in Ethiopia showed that food contamination with hazards is common in beef, poultry and vegetable food value chains (Gazu et al, 2023). The widespread contamination of foods with hazards in the country raises public health concerns, especially for vulnerable groups such as children, the elderly, pregnant women and the immunocompromised.…”
Section: Discussionsupporting
confidence: 89%
“…Such monitoring schemes need comprehensive information on food safety, including the risk of different foodborne hazards, to inform public health policies and implement interventions that contribute to reducing foodborne disease burden. Systematic reviews reporting food hazards have been conducted in some African countries to provide synthesized information on food contamination in these countries, which help inform policy and decision making by different stakeholders (Alonso et al, 2016;Paudyal et al, 2017;Oduori and Kwoba, 2022;Gazu et al, 2023). However, such information is lacking in Burkina Faso.…”
Section: Introductionmentioning
confidence: 99%
“…Consumption of uncooked meat as one of the risk factors for transmission of HEV was recorded at high rates in both research groups, and more than that, it gave a significant association (p-value = 0.005) with the positivity of anti-HEV IgG antibodies in the healthcare workers, this because Sudanese people, like many others around the world, are accustomed to eating parts of sheep and cow meat without cooking. It is known that consumption of uncooked meat is a major cause of zoonosis [34] and some infectious diseases [35]. In general, the serological frequency of HEV among healthcare workers recorded in this study is an indicator of the extent of the spread of HEV in the community, so necessary precautions to limit the spread of the disease such as community surveys and vaccination studies should be activated.…”
Section: Discussionmentioning
confidence: 79%
“…This was relatively lower than the prevalence of 20.6% reported by [8] in raw milk collected from different dairy farms in Ethiopia, and [42] also reported (61.2%) the prevalence of Campylobacter in raw milk samples collected from milk collection centers and (41.8%) in retail markets. Another study conducted by [14] also found that the prevalence of Campylobacter was 55.6% in milk collection centers and 16.7% in raw milk retail markets. [30], also found a 63.2% prevalence of Campylobacter in raw milk from collection centers and a 42.1% prevalence in retail markets.…”
Section: Discussionmentioning
confidence: 86%